High-resistance precision resistance alloy ultra-thin strip and preparation method thereof
Patent Information
- Application Number
- CN202611142325.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-30
AI Technical Summary
[0006]针对现有镍铬铝铜合金极薄带在厚度减薄至0.1mm以下时,因尺寸效应导致强塑性恶化、服役过程提前断裂,以及高电阻率与低电阻温度系数难以兼得的难题,本发明提供一种高阻值精密电阻合金极薄带及其制备方法
本发明方法采用“固溶+预时效处理+异步轧制+二次固溶退火+最终时效”的复合工艺路线。首先通过预时效促进基体中纳米级析出相的初步微量析出;随后利用异步轧制极强的轧薄能力,以及特有的强烈剪切变形和引入的复杂应力作用,有效改变合金极薄规格下的应力分布,减少边裂与断带,极大地提升减薄极限,实现了在无中间退火条件下连续稳定轧制至50μm以下的极薄规格。在此过程中,预时效微量析出相与强剪切变形产生的位错发生强烈的交互作用;尤为关键的是,在相同的压下率条件下,异步轧制特有的速度差诱导了强烈的附加剪切应变,使得带材内部产生的等效应变显著大于传统同步轧制,从而极大地促进了畸变能的高效积累。这种远高于传统同步轧制的高畸变能作为强驱动力,一方面显著促进了后续二次固溶短时退火过程中的完全再结晶与二次固溶效果,实现了晶粒的极致细化与均匀化;另一方面,在最终的时效处理中,均匀细小的组织与高密度晶体缺陷诱导析出相呈现超弥散、高均匀形态。这种微观组织的精确调控使最终产品抗拉强度达1000MPa~1100MPa的同时,断后伸长率仍保持在12%~14%;更重要的是,基体与析出相的均匀分布使电阻率稳定在1.58μΩ·m~1.94μΩ·m,因此,本发明在确保极薄带获得高强韧性的同时,实现了高电阻率与超低电阻温度系数的协同优化,极大增强了材料在微小型精密电子元器件服役中的批次一致性和长期稳定性。
Smart Images

Figure CN122625481B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal rolling, specifically relating to a high-resistance precision resistance alloy ultrathin strip and its preparation method. Background Technology
[0002] Ultra-thin high-resistivity precision resistor alloy strips are indispensable key materials for manufacturing high-precision, high-stability resistors, strain gauges, precision potentiometers, and various micro-electronic components. With the increasing demands for miniaturization, integration, and high reliability in fields such as electronics, instrumentation, and aerospace, extremely stringent requirements have been placed on the thickness, resistivity, temperature coefficient of resistance, and dimensional accuracy of the alloy strips used. Typically, the finished thickness of such ultra-thin strips needs to be controlled below 50 μm, with some high-end applications requiring less than 0.01 mm, while simultaneously possessing a high resistivity of over 1.3 μΩ·m and a resistance controlled within ±20 × 10⁻⁶. -6 It has a resistance temperature coefficient within ℃, as well as good mechanical properties and processability consistency.
[0003] Currently, the common process route for preparing such ultra-thin alloy strips is as follows: alloy ingots are obtained through vacuum melting, followed by hot forging and hot rolling to achieve the target thickness, and then gradually thinned to the desired thickness using a combination of repeated cold rolling and intermediate annealing. Commonly used alloy systems include nickel-chromium modified systems (such as Ni-Cr-Al-Cu, Ni-Cr-Mn-Si, etc.), iron-chromium-aluminum systems, and copper-manganese based systems. Among these, the nickel-chromium system achieves high resistivity and a low temperature coefficient by adding elements such as Al, Si, and Mn to form solid solution strengthening, supplemented by precipitation strengthening. In conventional preparation processes, multiple passes of cold rolling and intermediate annealing under a protective atmosphere are required to eliminate work hardening, regulate grain structure, and stabilize resistivity.
[0004] However, the traditional repeated cold rolling-intermediate annealing process reveals many insurmountable technical bottlenecks when manufacturing ultra-thin strips of high-resistivity alloys. First, high-resistivity alloys, due to their high solute atomic content and large lattice distortion, exhibit extremely high work hardening rates and show significant brittleness when cold-rolled to thin specifications. Edge cracks, strip breaks, and severe shape defects are easily generated during ultra-thin strip rolling, resulting in extremely low yields, especially when the thickness is reduced to below 0.02 mm, making continuous and stable rolling production almost impossible. Second, the intermediate annealing process struggles to balance softening and microstructure control. If the annealing temperature is too low, recrystallization is insufficient, and the alloy retains high hardness, leading to frequent strip breaks during subsequent rolling. If the annealing temperature is too high, the grains coarsen rapidly, causing uneven local deformation and deterioration of thickness tolerances in the ultra-thin strip. Furthermore, the micro-area resistivity characteristics are dispersed, and the temperature coefficient of resistance tends to drift excessively towards the positive direction, significantly reducing stability. Furthermore, alloys containing active elements such as Al and Si are prone to internal oxidation or surface component depletion during annealing, resulting in compositional and microstructural gradients on the strip surface, which severely affects batch-to-batch consistency and long-term stability of resistivity. In addition, to obtain the final high resistivity and low temperature coefficient, fine-scale graded aging heat treatment is usually required. However, heat treatment in the state of extremely thin strips is prone to defects such as adhesion, warping, and surface contamination, further reducing product yield and performance uniformity.
[0005] Existing technologies have explored non-traditional processes such as rapid solidification single-roll spinning and magnetron sputtering deposition to directly obtain thin-film resistance alloy materials. However, the thickness and width of the strips produced by rapid solidification are limited, and the surface quality and dimensional uniformity are difficult to meet the requirements of high-precision resistance elements. Sputtering deposition has a low deposition rate and high production cost, making it difficult to achieve large-scale industrial production with roll-to-roll lengths. Therefore, there is an urgent need for a method that can effectively overcome the defects of high-resistivity alloys, such as severe work hardening, frequent strip breakage during rolling, and difficulty in accurately controlling resistance performance, and can stably mass-produce ultra-thin resistance alloy strips with extremely thin thickness, high resistivity, high dimensional accuracy, and excellent and consistent temperature coefficient of resistance. Summary of the Invention
[0006] To address the challenges of existing nickel-chromium-aluminum-copper alloy ultrathin strips, where size effects lead to deterioration of strength and ductility, premature fracture during service, and the difficulty of simultaneously achieving high resistivity and a low temperature coefficient of resistance when the thickness is reduced to below 0.1 mm, this invention provides a high-resistivity precision resistance alloy ultrathin strip and its preparation method. This invention employs a composite process route of "solution treatment + pre-aging treatment + asynchronous rolling + secondary solution annealing + final aging" to prepare ultrathin strips with high toughness, high resistivity, and ultra-low temperature coefficient of resistance, achieving batch-to-batch consistency of resistive performance and long-term stability.
[0007] A high-resistance precision resistor alloy ultrathin strip and its preparation method, comprising the following steps: Step 1: Solution treatment; Using nickel-chromium-aluminum-copper alloy strip as raw material, with an initial thickness of 0.5mm to 0.8mm, solution treatment is carried out under a protective atmosphere, followed by water cooling to below 40℃ to obtain solution-treated nickel-chromium-aluminum-copper alloy strip.
[0008] Step 2: Pre-aging treatment; The strip obtained after solution treatment in step 1 is placed in a protective atmosphere for pre-aging treatment, and then water-cooled or air-cooled to room temperature, so that trace amounts of nanoscale phases are initially precipitated inside the alloy matrix.
[0009] Step 3: Asynchronous rolling; The pre-aged strip obtained in step 2 is placed on a cold rolling mill for asynchronous rolling. The speed ratio of the upper and lower work rolls is controlled at 1.05 to 1.30. After multiple rolling passes without intermediate annealing, the strip is rolled to a thickness of 50 μm to obtain an ultra-thin nickel-chromium-aluminum-copper alloy strip.
[0010] Step 4: Secondary solution annealing treatment; The nickel-chromium-aluminum-copper alloy ultrathin strip obtained in step 3 is placed in a protective atmosphere and subjected to a second solution annealing treatment to obtain an annealed nickel-chromium-aluminum-copper alloy ultrathin strip.
[0011] Step 5: Time-sensitive processing; The nickel-chromium-aluminum-copper alloy ultrathin strip obtained after the secondary solution annealing treatment in step 4 is subjected to aging treatment under a protective atmosphere to obtain the aged nickel-chromium-aluminum-copper alloy ultrathin strip product.
[0012] Further, the raw material in step 1 is a nickel-chromium-aluminum-copper alloy strip of grade 6J23, with an initial thickness preferably of 0.6 mm. The raw material, by mass percentage, comprises the following components: Cr: 19.0%–21.0%, Al: 2.70%–3.20%, Cu: 2.00%–3.00%, Mn: 0.50%–1.50%, C: ≤0.04%, Si: ≤0.20%, P: ≤0.01%, S: ≤0.01%, with the balance being Ni. The solution treatment temperature is 950℃–1150℃, and the time is 0.5 h–1.5 h.
[0013] Furthermore, the pre-aging treatment temperature in step 2 is 450℃~580℃, and the time is 0.5h~2h.
[0014] Furthermore, the asynchronous rolling described in step 3 uses a reversible four-roll cold rolling mill with a reduction rate of 5% to 15% per pass, and is lubricated by rolling oil or emulsion.
[0015] Furthermore, the secondary solution annealing temperature in step 4 is 900℃~1100℃, and the annealing time is controlled to be 3min~10min. The basis for limiting the short annealing time is as follows: on the one hand, since the strip thickness has been reduced to an extremely thin specification of less than 50μm after asynchronous rolling, the material has a large specific surface area and extremely fast thermal conduction response, and can fully complete recrystallization and secondary solution annealing in a short time of 3min~10min; on the other hand, short heating can effectively cut off the excessive grain engulfment and growth process, avoid grain coarsening at high temperature, thereby maximizing the fine grain strengthening effect and providing a uniform and fine microstructure matrix for the subsequent final aging. After annealing, the material is cooled to room temperature by water cooling to quickly lock in the secondary solution structure.
[0016] Furthermore, the aging treatment in step 5 is performed for 6 to 72 hours, preferably 12 to 24 hours, at a temperature of 500°C to 650°C, followed by water cooling to room temperature. By optimizing this aging time window, the precipitation kinetics of the nanoscale strengthening phase can be optimally matched with the matrix purification process. While ensuring the full release and stability of the microstructure and residual stress, it effectively avoids coarsening or aggregation of the precipitated phase due to over-aging, thereby ensuring that the temperature coefficient of resistance remains strictly stable within an extremely low ideal range.
[0017] A high-resistivity precision resistance alloy ultrathin strip, prepared using the above-described method, exhibits a tensile strength of 1000 MPa–1100 MPa, a yield strength of 589 MPa–634 MPa, an elongation after fracture of 12%–14%, a resistivity of 1.58 μΩ·m–1.94 μΩ·m, and an absolute value of 10 × 10⁻⁶ temperature coefficient of resistance. -6 / ℃~20×10 -6 / ℃.
[0018] The beneficial effects of this invention are: This invention employs a composite process route of "solution treatment + pre-aging treatment + asynchronous rolling + secondary solution annealing + final aging". First, pre-aging promotes the initial trace precipitation of nanoscale precipitates in the matrix. Then, utilizing the extremely strong thinning capability of asynchronous rolling, along with its unique intense shear deformation and the introduced complex stress, the stress distribution in ultra-thin alloy profiles is effectively altered, reducing edge cracks and strip breakage, significantly improving the thinning limit, and achieving continuous and stable rolling to ultra-thin profiles below 50 μm without intermediate annealing. During this process, the pre-aged trace precipitates interact strongly with the dislocations generated by the intense shear deformation. Crucially, under the same reduction rate, the unique speed difference of asynchronous rolling induces strong additional shear strain, resulting in a significantly greater equivalent strain within the strip than that generated by traditional synchronous rolling, thereby greatly promoting the efficient accumulation of distortion energy. This high distortion energy, far exceeding that of traditional synchronous rolling, serves as a powerful driving force. On one hand, it significantly promotes complete recrystallization and secondary solution treatment during the subsequent short-time annealing process, achieving extreme grain refinement and homogenization. On the other hand, in the final aging treatment, the uniform and fine microstructure and the high-density crystal defect-induced precipitates exhibit an ultra-dispersed and highly uniform morphology. This precise control of the microstructure enables the final product to achieve a tensile strength of 1000MPa to 1100MPa while maintaining an elongation at break of 12% to 14%. More importantly, the uniform distribution of the matrix and precipitates stabilizes the resistivity at 1.58μΩ·m to 1.94μΩ·m. Therefore, this invention achieves synergistic optimization of high resistivity and ultra-low temperature coefficient of resistance while ensuring high strength and toughness in ultra-thin strips, greatly enhancing the batch consistency and long-term stability of the material in the service of micro-miniature precision electronic components. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of a reversible four-roll mill, where R1 and R2 are the radii of the upper and lower working rolls, respectively, and V1 and V2 are the linear velocities of the upper and lower working rolls, respectively. Figure 2 The engineering stress-strain curve obtained after mechanical property testing of the nickel-chromium-aluminum-copper alloy ultrathin strip prepared in Example 1 of the present invention; Figure 3 The graph shows a comparison of the resistance performance of the high-resistivity nickel-chromium-aluminum-copper alloy ultrathin strip prepared in Example 1 of this invention with that of the raw material after resistance performance testing. Detailed Implementation
[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0021] To facilitate understanding of the present invention, several embodiments of the invention have been provided. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that the disclosure of the invention will be more thorough and complete.
[0022] Example 1 A high-resistance precision resistor alloy ultrathin strip and its preparation method, comprising the following steps: Step 1: Solution treatment; The raw material was a hard-rolled nickel-chromium-aluminum-copper alloy (6J23) strip with the following chemical element mass percentages: Cr: 19.8%, Al: 2.77%, Cu: 2.34%, Mn: 1.27%, C: ≤0.04%, Si: ≤0.20%, P: ≤0.01%, S: ≤0.01%, with the balance being Ni, and a thickness of 0.6 mm. The strip was solution-treated by heating to 1100℃ under a nitrogen protective atmosphere and holding for 1 hour, followed by water cooling to below 40℃ to obtain the solution-treated nickel-chromium-aluminum-copper alloy strip.
[0023] Step 2: Pre-aging treatment; The nickel-chromium-aluminum-copper alloy strip obtained in step 1 after solution treatment was placed in an argon protective atmosphere for pre-aging treatment at a temperature of 520°C for 1 hour, and then cooled to room temperature by water.
[0024] Step 3: Asynchronous rolling; A reversible four-roll cold rolling mill was used, with the speed ratio between the upper and lower rolls set to 1.30. The pre-aged nickel-chromium-aluminum-copper alloy ultra-thin strip obtained in step 2 was subjected to multi-pass asynchronous rolling, with a reduction rate of 5% to 15% per pass. No intermediate annealing was performed during the rolling process, and the strip was rolled into an ultra-thin strip with a thickness of 50 μm.
[0025] Step 4: Secondary solution annealing treatment; The nickel-chromium-aluminum-copper alloy ultrathin strip from step 3 was placed in a nitrogen protective atmosphere and subjected to a second solution annealing treatment at a temperature of 950°C for 3 minutes, followed by water cooling to room temperature.
[0026] Step 5: Time-sensitive processing; The ultrathin strip after the second solution annealing treatment in step 4 was aged under a nitrogen protective atmosphere at a temperature of 600℃ for 24 hours, and then water-cooled to room temperature.
[0027] The asynchronous rolling schematic diagram and the prepared 50μm thick nickel-chromium-aluminum-copper alloy ultrathin strip in this embodiment are shown below. Figure 1 As shown. The high-resistance precision resistor alloy ultrathin strip prepared in this embodiment was subjected to mechanical and physical property testing, and its engineering stress-strain curve is shown below. Figure 2 As shown, the resistance performance diagram is as follows: Figure 3 As shown, its tensile strength is 1058 MPa, yield strength is 633 MPa, elongation after fracture is 12.2%, resistivity is 1.76 μΩ·m, and temperature coefficient of resistance is ±10 × 10⁻⁶. -6 / ℃.
[0028] Example 2 A high-resistance precision resistor alloy ultrathin strip and its preparation method, comprising the following steps: Step 1: Solution treatment; The raw material is a hard-rolled nickel-chromium-aluminum-copper alloy (6J23) strip with the following chemical element mass percentages: Cr: 19.2%, Al: 3.15%, Cu: 2.10%, Mn: 0.65%, C: ≤0.04%, Si: ≤0.20%, P: ≤0.01%, S: ≤0.01%, with the balance being Ni, and a thickness of 0.6 mm. The strip is solution-treated by heating to 1000℃ under an argon protective atmosphere and holding for 1.5 h, followed by water cooling to below 40℃ to obtain the solution-treated nickel-chromium-aluminum-copper alloy strip.
[0029] Step 2: Pre-aging treatment; The nickel-chromium-aluminum-copper alloy strip obtained in step 1 after solution treatment was placed in an argon protective atmosphere for pre-aging treatment at a temperature of 500°C for 1 hour, and then water-cooled to room temperature.
[0030] Step 3: Asynchronous rolling; A reversible four-roll cold rolling mill was used, with the speed ratio between the upper and lower rolls set to 1.15. The pre-aged nickel-chromium-aluminum-copper alloy ultra-thin strip obtained in step 2 was subjected to multi-pass asynchronous rolling. The reduction rate of each pass was controlled between 5% and 15%. No intermediate annealing was performed during the rolling process, and the strip was rolled into an ultra-thin strip with a thickness of 50 μm.
[0031] Step 4: Secondary solution annealing treatment; The nickel-chromium-aluminum-copper alloy ultrathin strip from step 3 was subjected to a second solution annealing treatment under a nitrogen protective atmosphere. The second solution annealing temperature was 1000℃, the second solution annealing time was 5 minutes, and the cooling method was water cooling to room temperature.
[0032] Step 5: Time-sensitive processing; The nickel-chromium-aluminum-copper alloy ultrathin strip after secondary solution annealing was subjected to aging treatment under a nitrogen protective atmosphere. The aging treatment temperature was 550℃ and the aging treatment time was 12h. The cooling method was water cooling to room temperature.
[0033] The high-resistivity precision resistance alloy ultrathin strip prepared in this embodiment was subjected to mechanical and physical property testing. Its tensile strength was 1015 MPa, yield strength was 612 MPa, elongation after fracture was 13.2%, resistivity was 1.72 μΩ·m, and temperature coefficient of resistance was ±15 × 10⁻⁶. -6 / ℃.
[0034] Example 3 A high-resistance precision resistor alloy ultrathin strip and its preparation method, comprising the following steps: Step 1: Solution treatment; The raw material is a hard-rolled nickel-chromium-aluminum-copper alloy (6J23) strip with the following chemical element mass percentages: Cr: 20.5%, Al: 2.90%, Cu: 2.85%, Mn: 1.10%, C: ≤0.04%, Si: ≤0.20%, P: ≤0.01%, S: ≤0.01%, with the balance being Ni, and a thickness of 0.6 mm. The strip is solution-treated by heating to 1150℃ under a nitrogen protective atmosphere and holding for 0.5 h, followed by water cooling to below 40℃ to obtain the solution-treated nickel-chromium-aluminum-copper alloy strip.
[0035] Step 2: Pre-aging treatment; The nickel-chromium-aluminum-copper alloy strip obtained in step 1 after solution treatment was placed in an argon protective atmosphere for pre-aging treatment at a temperature of 550°C for 0.5 hours, followed by water cooling to room temperature.
[0036] Step 3: Asynchronous rolling; A reversible four-roll cold rolling mill was used, with the speed ratio between the upper and lower rolls set to 1.05. The pre-aged nickel-chromium-aluminum-copper alloy ultra-thin strip obtained in step 2 was subjected to multi-pass asynchronous rolling. The reduction rate of each pass was controlled between 5% and 15%. No intermediate annealing was performed during the rolling process, and the strip was rolled into an ultra-thin strip with a thickness of 50 μm.
[0037] Step 4: Secondary solution annealing treatment; The nickel-chromium-aluminum-copper alloy ultrathin strip from step 3 was subjected to a second solution annealing treatment under an argon protective atmosphere. The annealing temperature was 1050℃, the second solution annealing time was 8 minutes, and the cooling method was water cooling to room temperature.
[0038] Step 5: Time-sensitive processing; The nickel-chromium-aluminum-copper alloy ultrathin strip after the secondary solution annealing treatment in step 4 was subjected to aging treatment under a nitrogen protective atmosphere. The aging treatment temperature was 620℃ and the aging treatment time was 18h. The cooling method was water cooling to room temperature.
[0039] The high-resistivity precision resistance alloy ultrathin strip prepared in Example 3 was subjected to mechanical and physical property testing. Its tensile strength was 1023 MPa, yield strength was 615 MPa, elongation after fracture was 12.5%, resistivity was 1.85 μΩ·m, and temperature coefficient of resistance was ±20 × 10⁻⁶. -6 / ℃.
Claims
1. A method for preparing a high-resistance precision resistor alloy ultrathin strip, characterized in that, Includes the following steps: Step 1: Solution treatment; Using 6J23 grade nickel-chromium-aluminum-copper alloy strip as raw material, with an initial thickness of 0.6 mm, the composition by mass percentage is as follows: Cr: 19.0%~21.0%, Al: 2.70%~3.20%, Cu: 2.00%~3.00%, Mn: 0.50%~1.50%, C: ≤0.04%, Si: ≤0.20%, P: ≤0.01%, S: ≤0.01%, with the balance being Ni; the strip is solution-treated under a protective atmosphere and then water-cooled to below 40℃ to obtain the solution-treated nickel-chromium-aluminum-copper alloy strip. Step 2: Pre-aging treatment; The strip obtained after solution treatment in step 1 is placed in a protective atmosphere for pre-aging treatment, and then water-cooled or air-cooled to room temperature, so that trace amounts of nanoscale phases are initially precipitated inside the alloy matrix. Step 3: Asynchronous rolling; The pre-aged strip obtained in step 2 is placed on a reversible four-roll cold rolling mill for asynchronous rolling. The speed ratio of the upper and lower work rolls is controlled at 1.05 to 1.
30. After multiple rolling passes, the reduction rate of each pass is 5% to 15%. Rolling is lubricated with rolling oil or emulsion, and there is no intermediate annealing treatment. The strip is rolled to a thickness of 50 μm to obtain an ultra-thin nickel-chromium-aluminum-copper alloy strip. Step 4: Secondary solution annealing treatment; The nickel-chromium-aluminum-copper alloy ultra-thin strip obtained in step 3 is placed in a protective atmosphere and subjected to a second solution annealing treatment to obtain an annealed nickel-chromium-aluminum-copper alloy ultra-thin strip. Step 5: Time-sensitive processing; The nickel-chromium-aluminum-copper alloy ultrathin strip obtained after the secondary solution annealing treatment in step 4 is subjected to aging treatment under a protective atmosphere to obtain an aged nickel-chromium-aluminum-copper alloy ultrathin strip product; the resistivity of the aged nickel-chromium-aluminum-copper alloy ultrathin strip product is 1.58 μΩ·m~1.94 μΩ·m, and the absolute value of the temperature coefficient of resistance is 10×10⁻⁶. -6 / ℃~20×10 -6 / ℃.
2. The method for preparing a high-resistance precision resistor alloy ultrathin strip according to claim 1, characterized in that, The solution treatment in step 1 is performed at a temperature of 1000℃ to 1150℃ for a time of 0.5h to 1.5h.
3. The method for preparing a high-resistance precision resistor alloy ultrathin strip according to claim 1, characterized in that, The pre-aging treatment in step 2 is carried out at a temperature of 500℃ to 580℃ for a time of 0.5h to 2h.
4. The method for preparing a high-resistance precision resistor alloy ultrathin strip according to claim 1, characterized in that, The secondary solution annealing treatment in step 4 is carried out at a temperature of 950℃ to 1100℃, and the annealing time is controlled to be 3 min to 10 min.
5. The method for preparing a high-resistance precision resistor alloy ultrathin strip according to claim 1, characterized in that, The aging treatment in step 5 lasts for 12 to 24 hours at a temperature of 550°C to 650°C. After the aging treatment, the temperature is cooled to room temperature by water cooling.
6. A high-resistance precision resistor alloy ultrathin strip, characterized in that, The high-resistance precision resistance alloy ultra-thin strip is prepared by the preparation method of any one of claims 1-5, and has a tensile strength of 1000MPa to 1100MPa, a yield strength of 589MPa to 634MPa, and an elongation after fracture of 12% to 14%.
Citation Information
Patent Citations
Method for manufacturing ultra-thin nanocrystalline metal strip
CN105080966A
Preparation method of copper alloy strip with ultra-fine grain structure
CN122428221A